Understanding technology acceptance and use in social media platforms: a systematic literature review and the development of research framework - Roslan, Muhammad Amirul Asyraaf; Nasharuddin, Nurul Amelina; Azmi Murad, Masrah Azrifah (Tsinghua University Press, 2024)
The Systematic Literature Review (SLR) presented in the document focuses on the acceptance of social media (SM) platforms, particularly through the lens of the Unified Theory of Acceptance and Use of Technology (UTAUT), Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB) and other relevant theories. The review involves a comprehensive analysis of the most used theories of acceptance models, the methods for selecting studies, and the results and findings from the reviewed studies. The study also discusses the accomplishment of research goals and creates a research framework to guide future research. The geographic scope of the studies is also examined, providing insights into the distribution of studies across different countries. The review adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and meta-Analyses) guidelines for reporting systematic reviews and employs a theory-based approach, categorizing selected articles based on their theoretical foundations. The review's methodology involves the use of empirical evidence that meets predetermined inclusion criteria and addresses specific research questions. The document provides a detailed account of the steps involved in the systematic review, including the identification, screening, eligibility determination, and selection of studies. The review also offers implications for theory and practice, addresses limitations, and suggests areas for future research. © 2024 Tsinghua University Press.